More dangerous than dyads: how a third party enables rationalist explanations for war. (July 2017) - Gallop, Max
For the bargaining model of war, in the absence of incomplete information and commitment problems, war is irrational. But this finding rests on a simple and rarely discussed assumption, that bargaining is between exactly two participants. When we relax this assumption, in a three-player bargaining game, war is an equilibrium. Thus, a key finding of the bargaining model, that there is always an agreement that all states prefer war, is an artifact of dyadic analysis. By removing this limitation, we can find new factors that affect the risk of war: the number of actors, divergence in state preferences, alliance dynamics, and the issue being bargained over.